FROM ACTIONS TO IMPACT: A GUIDE TO EFFECTIVE ACTIVITY REPORTING - Klymenko, Tatiana (Collection of scientific papers «ΛΌГOΣ», 2025)
Inaccurate activity reporting can hinder project success, leading to misinterpretations of progress and ineffective decision-making. This document addresses this challenge by providing a practical framework for designing and reporting on activities in a way that accurately reflects project progress and impact. We will discuss best practices for defining measurable activities, selecting appropriate indicators, and ensuring that reporting clearly links activities to project goals and outcomes.